Implanting isolated Ru atoms into edge-rich carbon matrix for efficient electrocatalytic hydrogen evolution - Zhang, Huabin (2021)
Although the maximized dispersion of metal atoms has been realized in the single-atom catalysts, further improving the intrinsic activity of the catalysts is of vital importance. Here, the decoration of isolated Ru atoms into an edge-rich carbon matrix is reported for the electrocatalytic hydrogen evolution reaction. The developed catalyst displays high catalytic performance with low overpotentials of 63 and 102 mV for achieving the current densities of 10 and 50 mA cm , respectively. Its mass activity is about 9.6 times higher than that of the commercial Pt/C-20% catalyst at an overpotential of 100 mV. Experimental results and density functional theory calculations suggest that the edges in the carbon matrix enhance the local electric field at the Ru site and accelerate the reaction kinetics for the hydrogen evolution. The present work may provide insights into electrocatalytic behavior and guide the design of advanced electrocatalysts.